(untitled) (KYAMC Journal, 2019)
Introduction: Stroke is an important cause of disability among adults and is one of the leading causes of death worldwide. The reported prevalence of stroke in Bangladesh is 0.3%. Stroke patients have comorbidity Comorbidity is an important factor in stroke outcomes and burden. Objectives: This study was carried out with a view to find out the common comorbidities prevalent in stroke patients. Materials and Method: This cross sectional study was carried out in Faridpur Medical College Hospital from November 2018 to April 2019 to see the comorbidities and associated factors among admitted stroke patients. A total of 390 stroke patients were included. Data were collected by detailed history from patients or their relatives followed by thorough physical examination; Results: Among total respondents, majority was male (56.4%) and ischemic stroke was the commonest type of stroke (65.6%) diagnosed. The substantial number of patients (85.6%) had one or more comorbidities. Hypertension was the predominant comorbid condition (74.1%) followed by coronary heart disease ((19.5%), diabetes mellitus (17.4%), obesity (6.2%), hyperlipidemia (6.2%), CKD (4.9%), COPD (3.3%), malignancy (0.8%), hypothyroidism (0.5%),CLD (0.5%) and parkinsonism (0.3%). Comorbidities were present in 88.28% of ischemic stroke, 81.81% of intracerebral haemorrhage and 69.23% of subarachnoid hemorrhage cases. Patients with first stroke event have comorbidities in 83.64% cases where as in 95.45% cases of recurrent stroke patients. The relationship between comorbidity and mortality risk is not clear with approximately 16% death in both with or without comorbidity. Conclusion: The results of the study concluded that the prevalence of comorbidities in stroke patients remains high in our settings and the patients with increasing age and those with recurrent stroke events have statistically significant number of comorbid conditions. KYAMC Journal Vol. 10, No.-3, October 2019, Page 152-155